(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2020)
The Great Silk Road-a highway that since ancient times connects the West and East, is now becoming increasingly important. It is one of the best brands in the world. Kazakhstan section of the great silk road is a unique complex of monuments of history, archeology, architecture, urban planning and monumental art. But at the same time, the crossroads of the great silk road are the most popular routes and eco-tourism too. Ecotourism contributes to the conservation of nature and is becoming increasingly popular in the world. The transcontinental highway "Western Europe-Western China" passes through Kazakhstan, which opens the opportunity to touch the richness of nature and wisdom of history of the Great Silk Road. The particular importance of development of ecological tourism in specially protected natural areas, the concentration of recreational resources in places of historical and cultural heritage is acquiring. The article discusses the theoretical foundations of eco-tourism, the possibility of its organization in the Kazakh section of the Great Silk road. The advantages of its development are analyzed, the classification is developed and the SWOT-analysis of development of ecological tourism on The great Silk Road is made. At the same time, the prospects of development of ecological tourism on the Kazakhstan section of the great silk road are defined. Key words: tourism, ecotourism, types of tourism, national parks, silk road, landscapes, natural monuments.